Hydrolases in the hypopharyngeal glands of workers of Scaptotrigona postica and Apis mellifera (Hymenoptera, Apinae) - Costa, Rosiléia A. C. [UNESP]; Da Cruz-Landim, Carminda [UNESP] (My University, 2005)
Hydrolytic enzymes from hypopharyngeal gland extracts of newly emerged, nurse and foraging workers of two eusocial bees, Scaptotrigona postica, a native Brazilian stingless bee, and the Africanized honey bee (Apis mellifera) in Brazil, were compared. The hypopharyngeal gland is rich in enzymes in both species. Fifteen different enzymes were found in the extracts, with only a few quantitative differences between the species. Some of the enzymes present in the extracts may have intracellular functions, while others seem to be digestive enzymes. Scaptotrigona postica, had lower β-glucosidase and higher lipase esterase activities than A. mellifera. The differences may be due to different feeding habits and behavioral peculiarities of the two species. ©FUNPEC-RP.
Keywords: Africanized honeybee; Apidae; Apini; Enzymes; Esterase lipase; Glucosidases; Meliponini; Stingless bee; beta glucosidase; enzyme; esterase; hydrolase; bee; comparative study; enzyme activity; feeding behavior; honeybee; Hymenoptera; hypopharynx; nonhuman; quantitative analysis; Animals; Bees; Exocrine Glands; Female; Hydrolases; Hypopharynx; Apinae; Apis mellifera; Apoidea; Meliponinae; Scaptotrigona postica